(untitled) (Revista Cocar, 2020)
Anísio Teixeira and the embate with catholics: the educational debate (1957-1961) Resumo O presente artigo apresenta como objetivo a análise das propostas do intelectual Anísio Teixeira no debate educacional com os segmentos privatistas, tendo a frente os intelectuais católicos, entre os anos de 1957 a 1961, período marcado por intensas disputas em relação à primeira Lei de Diretrizes e Bases da Educação, aprovada em 21 de dezembro de 1961. Trata-se de uma análise histórica, bibliográfica e documental, por meio do levantamento de fontes primárias: Jornal A hora; A Folha da Manhã; A Noite, entre outros, subsidiada pelo referencial teórico do materialismo histórico dialético. Nesses termos, ao se analisar as propostas presentes no debate articulado à totalidade histórica do período, verificou-se que Anísio Teixeira e os defensores da escola privada, em que pese as diferenças, defendiam a ordem estabelecida. Palavras-chave: Anísio Teixeira. Católicos e liberais. LDB 4024/61. Abstract The objective of this article is to analyze the proposals of the intellectual Anísio Teixeira in the educational debate with the privatist segments, with the Catholic intellectuals ahead, between the years of 1957 and 1961, a period marked by intense disputes over the first Law of Guidelines and Bases of Education, approved on December 21, 1961. This is a historical, bibliographical and documentary analysis, through the survey of primary sources: Jornal A hora; The Leaf of the Morning; The Night, among others, subsidized by the theoretical reference of dialectical historical materialism. In these terms, when analyzing the proposals present in the debate articulated to the historical totality of the period, it was verified that Anísio Teixeira and the defenders of the private school, in spite of the differences, defended the established order. Key-words: Anísio Teixeira. Catholics and liberals. LDB 4024/61.